Influence of Service Quality, Brand Image and Customer Relationship Management (CRM) on Customer Loyalty - Sri Astuti; R A Marlien (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of service quality, brand image, and customer relationship management on customer loyalty. The sampling technique used by the researcher was purposive sampling. The population in this study was all 105 cooperative customers, respondents with data analysis using multiple regression. Findings in this research. `Service quality and CRM have a positive and significant effect on customer loyalty where the dominant influence is service quality. Brand Image has a negative and insignificant effect on Customer Loyalty.